An evaluation of the application of e-logistics in organization - Lim, Gaik Shu; Razalli, Mohd Rizal (2012)
The purpose of the study is to provide a better understanding of how organizations utilize e-logistics within their supply chain.Two questions will be examined, (1) How can the e-Logistics system be described and (2) What the factors that influence the e-logistics system.The e-Logistics system can be described as a process and as an information system.Factors then include reliability factors, maintainability factors, supply support factors, test and support equipment factors, organizational factors, facility, transportation, and handling factors, software factors, availability factors, and economic and effectiveness factors. These factors, however, deserves further research.